Functional perspectives in mental jigsaw puzzles: Insights from eye-tracking, questionnaire, and behavioral data - Tsuyoshi Yoshioka; Hiroyuki Muto; Jun Saiki (PLoS ONE, 2025)
This study investigated cognitive strategies in mental jigsaw puzzles, integrating mental rotation and translation with a focus on directionality and detour arguments. Unlike object mental rotation tasks, these puzzles introduced physical constraints, revealing systematic directional tendencies in both eye movements and subjective reports. Specifically, smaller protruding objects were consistently directed toward larger indented objects. This was accompanied by longer completion times and reduced linearity, paralleling strategies used in physical puzzle-solving. Behavioral asymmetries observed in the puzzles unexpectedly mirrored those found in object mental rotation tasks. While controlling for mental motion directions showed comparable completion times at 300° between tasks, the study did not fully clarify the role of detours, indicating the need for further research.